2021
DOI: 10.2465/jmps.200916
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of supracrustal rocks of the Indochina Block: Evidence from new detrital zircon U–Pb ages of the Kontum Massif, Central Vietnam

Abstract: The Kontum Massif and the Truong Son Belt, central Vietnam are the magmatic-metamorphic massifs (belts) of the Indochina Block. These two massifs (belts) underwent two independent orogenic events during Ordovician-Silurian and Permian-Triassic ages. However, due to the strong overprint of these two orogenic events, the evidence of any preexisting (e.g., Precambrian) tectono-thermal events have become extremely poor. Hence, the Precambrian age components of the Indochina Block have not been fully revealed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…(a–d) Synthesis and comparison of Kernel Density Estimate (KDE) diagrams of detrital zircon U–Pb ages. (a) Lingwen Formation (this study); (b) central Vietnam (data from Kenta et al, 2021); (c) west of the Ailaoshan fault (data from Halpin et al, 2016; Liu, Peng, et al, 2022; Xu, Xia, Lai, Long, & Huang, 2019); (d) southwest margin of the SCB (data from Chai et al, 2022; Duan et al, 2018; Hu et al, 2017; Liu, Peng, et al, 2022; Xu, Xia, Lai, Long, & Huang, 2019; Yang et al, 2012a); (e) southeast margin of the SCB (Hu et al, 2015; Kong, Xu, Tao, et al, 2022; Xu et al, 2018). MDS diagram based on Cross‐correlation, Likeness, Kuiper test V value and K–S test D value (e–h), the solid line represents the closest neighbour.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…(a–d) Synthesis and comparison of Kernel Density Estimate (KDE) diagrams of detrital zircon U–Pb ages. (a) Lingwen Formation (this study); (b) central Vietnam (data from Kenta et al, 2021); (c) west of the Ailaoshan fault (data from Halpin et al, 2016; Liu, Peng, et al, 2022; Xu, Xia, Lai, Long, & Huang, 2019); (d) southwest margin of the SCB (data from Chai et al, 2022; Duan et al, 2018; Hu et al, 2017; Liu, Peng, et al, 2022; Xu, Xia, Lai, Long, & Huang, 2019; Yang et al, 2012a); (e) southeast margin of the SCB (Hu et al, 2015; Kong, Xu, Tao, et al, 2022; Xu et al, 2018). MDS diagram based on Cross‐correlation, Likeness, Kuiper test V value and K–S test D value (e–h), the solid line represents the closest neighbour.…”
Section: Discussionmentioning
confidence: 74%
“…However, previous studies have not identified Neoproterozoic magmatic rocks on Hainan Island. Detrital zircons of this age group are also rare in clastic rock from the Truong Son belt and the Kontum Massif in the IB (Kenta et al, 2021; Wang, Lin, Faure, Lepvrier, et al, 2021; Wang, Zhang, Qian, Wang, et al, 2021). However, detrital zircons aged 750–1000 Ma were present in the SCB (Liu, Hu, Chen, et al, 2021; Wang et al, 2019; Wang, Wen, et al, 2018; Zhou, Liang, Liang, Jiang, Wang, et al, 2015b), indicating that the surrounding SCB and Yangtze Craton were the source areas for Hainan Island during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geologists from Vietnam and abroad argue that the Indochina block consists of three main structural zones on Vietnamese territory: the Kontum massif in central Vietnam, the Da Lat zone in the south, and the TS belt in the north [3,9,[16][17][18] (Figure 1a). The Song Ma suture borders to the northern margin of the TS belt, which is located in north-central Vietnam [1,2,5,[19][20][21][22].…”
Section: Regional Geology and Petrographymentioning
confidence: 99%
“…Zircon separation and mount‐making processes are the same as those described in Kawaguchi, Minh, Hieu, Cuong, and Das (2021). Zircon separation was accompanied by the panning method using the whole‐rock powder with water.…”
Section: Sampling Field Relationships and Analytical Techniquesmentioning
confidence: 99%